Typical stages in industries' e-transformation – hints for forecasting future entrepreneurial challenges in revenue management. (24th October 2007) - Gersch, Martin; Goeke, Christian
One specific form of industry transformation process is the so-called e-transformation, which focuses on the impacts of digitalisation and interconnectedness. Over the course of an industry sector's e-transformation, four characteristic stages of development can be identified to show particular entrepreneurial challenges: channel enhancement, value chain integration, industry transformation, and convergence. This paper investigates these particular stages, which have an impact on a company's revenue management. It finishes with a comprehensive case study concerning the shift of Germany's healthcare sector from the stage of value chain integration to industry transformation and corresponding changes in revenue models.